2008
DOI: 10.1111/j.1572-0241.2008.01824.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Established Simple Office-Based Immunological FOBT With Fecal Tumor Pyruvate Kinase Type M2 (M2-PK) for Colorectal Cancer Screening: Prospective Multicenter Study

Abstract: This office-based IFOBT was found to have significantly higher specificity, PPV, and positive LR as compared with M2-PK. IFOBT proved to be a convenient, noncumbersome, quick, and cheap tool in patients with above-average risk for detection of CRN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 44 publications
2
51
0
2
Order By: Relevance
“…Their study further supports the previous smaller studies in patients with more-than-average risk of harbouring colorectal cancer (CRC) (Shastri et al, 2006(Shastri et al, , 2008, in which the suboptimal performances of faecal pyruvate kinase M2 (M2-PK) for detecting the precursors for CRC (the colorectal adenomas) have already been demonstrated. However, we have certain comments to make about this study:…”
Section: Sirsupporting
confidence: 86%
“…Their study further supports the previous smaller studies in patients with more-than-average risk of harbouring colorectal cancer (CRC) (Shastri et al, 2006(Shastri et al, , 2008, in which the suboptimal performances of faecal pyruvate kinase M2 (M2-PK) for detecting the precursors for CRC (the colorectal adenomas) have already been demonstrated. However, we have certain comments to make about this study:…”
Section: Sirsupporting
confidence: 86%
“…However, results were obtained on a sample size of 5 patients. When Shastri and colleagues (29) conducted sensitivities of M2-PK for adenoma detection for a larger sample size, sensitivities obtained were much lower at 37%.…”
Section: Fecal Biomarkersmentioning
confidence: 98%
“…These studies used a sandwich ELISA to measure TuM2-PK activity, obtaining overall sensitivities ranging from 68% to 91%. In the 2 studies by Shastri and colleagues (29,33), they compared tumor M2-PK activity and guaiac based FOBT in the first study and subsequently immunologic FOBT in the second study. They found that although measuring tumor M2-PK activity was more sensitive than FOBT screening, when compared with iFOBT, the latter was more sensitive, cheaper, and faster than tumor M2-PK activity assays.…”
Section: Fecal Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In two studies tumor pyruvate kinase isoenzyme M2 was shown to have no supplemental value for screening because of a lower sensitivity and specificity [27,28] compared to iFOBT.…”
Section: Immunological Fecal Occult Blood Testmentioning
confidence: 99%